Glycogen storage disorder Type IXa and congenital hypothyroidism: A novel association - Hosaagrahara Ramakrishna, Somashekara; Nargund, Spoorthi; Kannan, Subramanian (Indian Journal of Child Health, 2020)
Glycogen storage disease (GSD) is a disorder of glycogen metabolism and GSDs are classified according to the enzyme deficiency and the affected tissue. Previously, an association of thyroid autoimmunity and hypothyroidism in patients with GSD has been reported. Here, we are presenting a rare association of congenital hypothyroidism with GSD IXa in a child who presented with progressive abdominal distension and hepatomegaly. GSD was suspected clinically and was confirmed by whole-exome sequencing